Plurale Autorschaft (De Gruyter, 2024)
The contributions in this volume examine the aesthetics of plural authorship from the disciplinary and interdisciplinary perspectives of literary studies, art history, and musicology. The volume aims to analyze plural authorship in the pre-modern era as a coordinate of a different aesthetics and to contextualize it within the history of culture.